Raising production and productivity of rice-based cropping systems through Rice Crop Manager in India - CGIAR Research Program on Rice (2019)
Rice Crop Manager is a decision-support tool designed for use by extension workers, crop advisors, agricultural service providers and farmer leaders. It is accessible online on personal computers, tablets or smartphones. In India to date, 175,000 farmers have received recommendations.